Patterns of ecology and distribution of the tree crickets Oecanthus dulcisonans and O. pellucens (Orthoptera: Gryllidae; Oecanthinae) in southern Italy - Labadessa, Rocco; Todisco, Simone (Zootaxa, 2016)
Ecological proclivities of the tree cricket Oecanthus dulcisonans, which has been recently separated from the well known O. pellucens, have been poorly investigated. Moreover, studies on the patterns driving niche segregation between these related species are still needed. This study aims to explore the role of macro-habitat in shaping the distribution of O. dulcisonans and O. pellucens in southern Italy. Occurrence data were sampled by means of a rapid acoustic survey scheme at a regional scale. The significance of difference in ecological and habitat parameters was tested between the two species. While confirming species behavioural patterns, new findings are provided with regard to their ecological difference. Species distribution proves to be primarily driven by elevation gradient and temperature variation, with O. dulcisonans common and widespread in warmer lowlands and O. pellucens limited to higher altitudes. The two species also show significant spatial segregation within vegetation layers. These findings also provide cues for future studies on species interaction, as well as for the assessment of a monitoring scheme which may help interpreting the effects of broad environmental changes.